The role of Quality Control in improving the Quality of Learning with competitive advantage at MTs Darul Hikmah Tulungagung and MTs Maarif NU 2 Sutojayan Blitar - Rohmawati, Eti; Maftukhin, Maftukhin; Akhkyak, Akhkyak; Fuadi, Imam; Muthohar, Prim Masrokhan (Technium Social Sciences Journal, 2022)
Quality learning is the main factor in encouraging educational progress. Quality education will be chosen by the community. Learning quality control is important in managing and improving the quality of learning so that better output is produced at the institution. MTs Darul Hikmah Tulungagung and MTs Ma’arif NU 2 Sutojayan Blitar are able to provide quality learning services by increasing quality control in learning to meet the needs and demands of stakeholders so that they are able to have achievements, have advantages, and have trust in the community